Abusus Iuris and the Protection of Public Interest by Administrative Authorities and (Administrative) Courts in Slovakia - Potasch, Peter (Public Governance, Administration and Finances Law Review, 2018)
The presented paper deals with public interest in the decision-making practice of public authorities. The author also deals with the so-called abusus iuris (with focus on public law) which does not enjoy legal protection on the grounds that it is contrary to public interest. In this context, the author also points out that there is no uniform and universal definition of the concept/term of “public interest”, but that public interest as such consists of partial public interests which may sometimes even be in conflict with one another thus comparing public interest and private interest in a certain case does not always have to suffice. He also points out certain procedural burdens relating to administrative proceedings – in particular the burden of sufficient reasoning and fact-finding especially in reference to the protection of public interest by administrative authorities. The paper primarily focuses on the decision-making practice of the courts of the Slovak Republic and of the Czech Republic – both at the level of protection of public interest in administrative proceedings and of its protection in court proceedings.